Implementation of Hadith as a Foundation for Deradicalization in Contemporary Islamic Education Curriculum - Yusuf, M. Fajri; Siregar, Bona Bargot Riezky Nagabe; Harahap, Alwi Padly (Universitas Nurul Jadid, 2024)
Radicalism and religious extremism have become global issues that pose significant challenges to the world of education, especially in the context of Islam. Islamic education is one of the most effective tools to counter radicalism. However, an overly rigid and dogmatic approach to education can sometimes exacerbate the problem. This study aims to build a hadith-based curriculum as a foundation for deradicalization. This study uses a qualitative method with descriptive-analytic data analysis techniques. The study’s results indicate several hadiths that, if integrated into the Islamic education curriculum, can strengthen the values of peace, and tolerance, and prevent radicalism. Implementing these hadiths in educational materials can provide a more balanced understanding of religion and foster critical attitudes and tolerance among students. Effective implementation requires the selection of relevant hadiths, contextual interpretation, development of teaching materials, and good teacher training. This study is expected to provide specific benefits for educational institutions in designing a curriculum that functions as an instrument for deradicalization based on religious teachings. Thus, this study contributes to creating a generation that is moral, tolerant, and able to face global challenges without losing its moderate religious identity.